Effect of side groups on glass transition temperatures of Poly(ethoxy/phenoxy)phosphazenes: Prediction and synthesis. (16th September 2021) - Wang, Jiachen; Li, Zhanqiang; Basharat, Majid; Wu, Shaojun; Zhang, Shuangkun; Zhang, Xinfang; Ma, Hanlin; Liu, Wei; Wu, Dezhen; Wu, Zhanpeng
Abstract: Poly(aryloxyphosphazenes) are thermally stable, insulative, fire proof, and ablative resistant in extreme combustion, and can be applied as an insulated covering of high voltage cable and thermal shielding material for aircraft and spacecraft. However, being an elastomer, its higher glass transition temperature ( T g above −15 °C) limits the application in certain aspects. Therefore, adjustment of the T g of poly(aryloxyphosphazenes) has become a research focus to improve overall performance. Introducing substituents such as alkoxy groups has been identified as an effective approach to lower the polymer T g . In this study, based on the introduction of the different ratios of the ethoxy substituents in poly(bisphenoxyphosphazene), a series of simulations and experimental studies have been carried out for predicting the T g of polyphosphazenes, along with establishing the relationships among synthesis, structure, and T g . Molecular dynamics (MD) simulations using COMPASS force field and empirical Flory-Fox equation have been used to predict the T g of the polymers and confirm the compatibility with the experimental data. Overall, the simulation results are noted to be in good agreement with the experimental values, and the T g of the polymers gradually decreases with an increase in the ethoxy content. The proposed methods are efficient for the prediction of the T g values of polyphosphazenes and can also be used for the structure prediction via the desired T g, which is likely to have broad application for targeted polyphosphazenes synthesis. Graphical abstract: Image 1 Highlights: The T g s of polyphosphazenes are predict by Molecular Dynamics and Fox equation. The T g of polyphenoxyphosphanzene is tuned down by incorporation of ethoxy. The relationships among PEPPs' synthesis, structure and T g are established. The predictions are in good agreement with the experimental values of synthesized PEPPs.